Awareness of Custom officers on Counterfeit pharmaceutical products and the roles of pharmacy enforcement officers - Chuo, Yew Ting; Hiram, Ting; Yee, Chang Soh; Abu Hassan, AAJ; Kah, Seng Lee (EManuscript Services, 2017)
Background: Counterfeit pharmaceutical products (CPP) is a lucrative business for illegal operators who constantly try to smuggle their products into Malaysia. Full understanding of the roles and duties of pharmacy enforcement division as well as CPP by Royal Malaysian Custom (RMC) officers are pre-emptive to optimize the operation against drug smuggling. Objective: This study is aimed to examine the awareness of RMC officers on CPP and the roles of Pharmacy Enforcement Division (PED) officers at custom ports. Methods: A self-administered structured questionnaire was developed based on the review of relevant Acts and Guidelines. The questionnaire was reviewed by 4 key officers and pre-tested. Stratified purposeful sampling was adopted to recruit RMC officers who worked at 16 custom ports in Sarawak where PED officers were stationed. Ethics approval and permission to collect data were obtained prior to data collection. Results: A total of 110 RMC respondents (48.9% response rate) were sampled. As a whole, the mean scores of awareness level towards CPP and the roles of PED officers are satisfactory at 4.12 (±SD 0.967) and 4.21 (±SD 0.785) respectively. RMC officers who have worked for more than 10 years are significantly having greater awareness towards CPP as compared to those who have worked for 10 years or less. Conclusion: This study reveals that the awareness of RMC officers towards CPP and the roles of PED officers are sufficient to curb the entering of CPP through the collaboration of PED officers. However, the awareness program for the RMC officers who have less experience is necessary to reinforce their understanding of CPP.